Low-content barium doping induces two-phase coexistence in NaNbO3 to enhance the piezo–photocatalytic activity. Issue 24 (15th December 2022) - Li, Li; Cao, Wenjun; Liu, Wei; Liang, Cen; Shi, Xingyu; Li, Feng; Wang, Chunchang
Abstract: Piezo–photocatalysis induced by ultrasound vibration and light irradiation is an emerging strategy to decelerate the rapid recombination of photoinduced charges in the catalytic process. Element doping-induced structural phase transition is an effective approach to improve catalytic performance. Herein, barium (Ba) doped sodium niobate (abbreviated as Na1-2x Bax NbO3, x = 0, 0.005, 0.010, 0.015, and 0.020) nanomaterials were successfully prepared by a water-based sol-gel method. With the increase of Ba content, the morphology changes from sphere to cubic, and the orthorhombic NaNbO3 transforms to an orthorhombic–cubic mixed phase. Compared with the single orthorhombic phase NaNbO3, the piezo–photocatalytic degradation ratio of mixed-phase Na0.97 Ba0.015 NbO3 is enhanced by 16% in the decomposing of Rhodamine B (RhB), and the kinetic rate constant is up to 0.0114 min −1, which is 1.65 times higher than that of the orthorhombic NaNbO3 . The improved piezo–photocatalytic activity is attributed to the two-phase coexistence and optimum amount of oxygen vacancies. In addition, the photocatalytic, piezocatalytic, and piezo−photocatalytic performances and mechanisms of the Na0.97 Ba0.015 NbO3 sample were also investigated. This work provides a reference for the construction of structural phase and the practical application of the piezo–photocatalysis in the environmental field.